1993
DOI: 10.3109/15563659309000396
|View full text |Cite
|
Sign up to set email alerts
|

The Price of Gold: Mercury Exposure in the Amazonian Rain Forest

Abstract: Concern has surfaced over the recent discovery of human mercury exposure throughout the tropical rain forest of South America's Amazon River Basin. The probable source of mercury has been traced to gold mines located within the interior. The mining process involves the extraction of gold from ore by burning off a mercury additive, resulting in vaporization of elemental mercury into the surrounding environment. The purpose of this case series is to document mercury levels in miners and local villagers presentin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
3

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 15 publications
3
57
0
3
Order By: Relevance
“…These data are consistent with reports by others on occupational exposures to mercury in artisanal gold mining in Amazônia. Branches et al (1993) 5 reported somewhat lower exposures among goldmines in Pará in 1993; a similar range of nonspecific symptoms were also reported in these subjects, as well as signs of neurological dysfunction by clinical examination. We are unaware of any cases of clinical mercury poisoning having been reported in the published literature in gold miners in Pará to date.…”
Section: Resultsmentioning
confidence: 77%
“…These data are consistent with reports by others on occupational exposures to mercury in artisanal gold mining in Amazônia. Branches et al (1993) 5 reported somewhat lower exposures among goldmines in Pará in 1993; a similar range of nonspecific symptoms were also reported in these subjects, as well as signs of neurological dysfunction by clinical examination. We are unaware of any cases of clinical mercury poisoning having been reported in the published literature in gold miners in Pará to date.…”
Section: Resultsmentioning
confidence: 77%
“…The first study on clinical signs and symptoms emphasized prospectors, gold shop workers, and riverside communities in the Tapajós Basin, with the first reports of suspected cases of mercury poisoning between 1986 and 1991 10 . The study assessed Hg levels in blood and urine samples and included motor coordination tests.…”
Section: Introductionmentioning
confidence: 99%
“…No sangue, o mercúrio é oxidado pelos eritrócitos (células vermelhas do sangue) e, uma vez oxidado, o íon Hg 2+ é rapidamente distribuído pelo corpo através do sangue, podendo se ligar também à albumina e à hemoglobina 1 . Os principais sintomas associados à toxicidade por exposição ao mercúrio incluem tremor, vertigem, entorpecimento, dor de cabeça, cãibra, fraqueza, depressão, distúrbios visuais, dispnéia, tosse, inflamações gastrointestinais, queda de cabelo, naúsea e vômitos 1,17 .…”
Section: Toxicidade Do Mercúriounclassified